Azolla Compost as an Approach for Enhancing Growth, Productivity and Nutrient Uptake of Oryza sativa L. - Mahmoud F. Seleiman; Omnia M. Elshayb; Abdelwahed M. Nada; Sara A. El-leithy; Lina Baz; Bushra A. Alhammad; Ayman H. A. Mahdi (Agronomy, 2022)
The excessive application of synthetic fertilizers can result in severe environmental risks, while composting green and fresh feedstocks can provide slow-release nutrients. Therefore, the aim of the current investigation was to study the effects of eight individual and combination treatments of azolla compost and NPK synthetic fertilizers (control = no fertilizer and compost; 100% NPK = full recommended dose of synthetic fertilizers as follows: 165 kg N ha−1, 37 kg P2O5 ha−1 and 50 kg K2O ha−1; 70% NPK; 40% NPK; 100% azolla compost (5 t DM ha−1); 50% NPK + 50% azolla compost; 70% NPK + 30% azolla compost and 40% NPK + 60% azolla compost) on rice growth, productivity and nutrient uptake in semi-arid agro-ecosystems. The results indicated that the combination of 40% NPK + 60% azolla compost or 50% NPK + 50% azolla compost resulted in the most optimal growth and the highest yield components. In addition, the application of 40% NPK + 60% azolla compost exhibited similar rice grain yields (10.76 t ha−1) as well as N, P, and K content and uptake compared with the full recommended dose of NPK fertilizer (100% NPK). This study declared that the utilization of azolla compost as an individual or combination application can reduce usage of synthetic fertilizers by up to 60% without significant reduction in the growth and grain productivity of rice.